ENVIRONMENTAL AND SOCIAL REPORTING IN CRISIS: LESSONS FROM ESG CONTROVERSIES AND SCANDALS - Irfan, Andi; Suminaringtias, Ratna (J-MIND (Jurnal Manajemen Indonesia), 2024)
Issues such as economic crisis, global warming, ideas of sustainability and governance have seen strong growth and improvement in the industry. The ESG (environmental, social, governance) index has attracted investors' attention to sustainable investment practices and measures the performance of companies' sustainability reports. Despite growing attention to environmental, social and governance (ESG) practices, little is known about the financial impact of poor social performance. Therefore, this research aims to highlight cases related to ESG controversies that occur in companies around the world. ESG controversies are defined as corporate ESG news such as suspicious social behavior and product defect scandals that put a company under the media spotlight and, furthermore, attract the attention of investors. This research aims to highlight cases related to ESG controversies that occur in companies throughout the world. To mitigate and avoid phenomena related to controversy, the role of business ethics is needed.